2016
DOI: 10.3389/fchem.2016.00037
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine A2B Receptor: From Cell Biology to Human Diseases

Abstract: Extracellular adenosine is a ubiquitous signaling molecule that modulates a wide array of biological processes. Recently, significant advances have been made in our understanding of A2B adenosine receptor (A2BAR). In this review, we first summarize some of the general characteristics of A2BAR, and then we describe the multiple binding partners of the receptor, such as newly identified α-actinin-1 and p105, and discuss how these associated proteins could modulate A2BAR's functions, including certain seemingly p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(54 citation statements)
references
References 149 publications
(191 reference statements)
0
51
0
Order By: Relevance
“…A 2B AR is highly expressed in tumor cells and promotes tumor cell proliferation; hence, it might serve as a target for novel therapies or combination therapies for cancer [249]. A 2B AR promoted tumor-inducing M2 macrophages (tumor-associated macrophages); however, it had less effect on decreasing cancer cell proliferation and metastasis and inducing proapoptotic effects [250].…”
Section: A 2b Ar In Cancermentioning
confidence: 99%
“…A 2B AR is highly expressed in tumor cells and promotes tumor cell proliferation; hence, it might serve as a target for novel therapies or combination therapies for cancer [249]. A 2B AR promoted tumor-inducing M2 macrophages (tumor-associated macrophages); however, it had less effect on decreasing cancer cell proliferation and metastasis and inducing proapoptotic effects [250].…”
Section: A 2b Ar In Cancermentioning
confidence: 99%
“…Then, firstly the extracellular pool of adenosine is reduced mainly through nucleoside transporters that transport it back into the cell; secondly, adenosine is deaminated to inosine through the action of adenosine deaminase. Finally, adenosine could be deactivated by its phosphorylation in AMP through the action of adenosine kinase [6]. Adenosine acts via specific receptors that are divided into at least four categories: A(1), A(2A), A(2B) and A(3) [7].…”
Section: Overviewmentioning
confidence: 99%
“…A2b receptor can be expressed in a variety of tissue such as vasculature, brain, intestines and on many cell types including mostly immune cells such as mast cells, neutrophils, dendritic cells, macrophages and lymphocytes, but also other cells like endothelial cells, astrocytes and neurons 46 . Its widespread expression as well as its diversity in signaling places A2b as an important player in numerous diseases such as vascular diseases, chronic and acute lung disease, renal disease and diabetes and cancer 46 . Many studies have demonstrated A2b receptor to be pro‐tumorigenic.…”
Section: A2b Receptor In Cancermentioning
confidence: 99%